2016
DOI: 10.22216/jen.v1i1.1030
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendidikan Kesehatan Tentang Latihan Range of Motion (ROM) Terhadap Keterampilan Keluarga Dalam Melakukan ROM Pada Pasien Stroke Di Bangsal Syaraf RSUP Dr M.Jamil Padang Tahun 2013

Abstract: ABSTRAK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Namely, there were 11 respondents on a scale of 3 and 17 respondents on a scale of 4; after the Range of Motion was carried out, the respondents experienced an increase in muscle strength on a scale of 4, totaling 25 respondents. Agonwardi and Budi (2016) said that Range of Motion (ROM) exercises could be useful for maintaining and improving the ability to move joints normally and completely to increase muscle mass and tone. This statement has similarities with the results of Basuki's research (2018) that the application of ROM is very effective for patients who experience post-stroke muscle weakness.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, there were 11 respondents on a scale of 3 and 17 respondents on a scale of 4; after the Range of Motion was carried out, the respondents experienced an increase in muscle strength on a scale of 4, totaling 25 respondents. Agonwardi and Budi (2016) said that Range of Motion (ROM) exercises could be useful for maintaining and improving the ability to move joints normally and completely to increase muscle mass and tone. This statement has similarities with the results of Basuki's research (2018) that the application of ROM is very effective for patients who experience post-stroke muscle weakness.…”
Section: Introductionmentioning
confidence: 99%
“…25 The results of the study conducted at the RSUP Dr. M. Djamil, Padang, Indonesia, showed that nurses only teach families right and left sloping mobilization to prevent decubitus in patients with stroke. 26 Other studies 27 suggested that providing a 7-week supportive-educative program significantly improves dietary control, exercise, medication use, stress management, and personal hygiene behavior in patients with type 2 Diabetes Melitus (DM) compared with the group that did not undergo a supportive-educative program. 28 also reported that using a self-care model that involved 30 en 45 minutes training sessions could improve all dimensions of quality of life in patients with migraine.…”
Section: Introductionmentioning
confidence: 99%